Incorporating dynamic factors for improving a GIS‐based solar radiation model. Issue 2 (2nd January 2020) - Zhang, Mingxi; Wang, Bin; Liu, De Li; Liu, Jiandong; Zhang, Hong; Feng, Puyu; Kong, Dongdong; Cleverly, James; Yang, Xihua; Yu, Qiang
Abstract: Solar radiation has been a major input to agricultural, hydrological, and ecological modeling. However, solar radiation is usually influenced by three groups of dynamic factors: sun–earth position, terrain, and atmospheric effects. Therefore, an integrated approach to accurately consider the impacts of those dynamic factors on solar radiation is essential to estimate solar radiation over rugged terrain. In this study, a spatial and temporal gap‐filling algorithm was proposed to obtain a seamless daily MODIS albedo dataset. A 1 km‐resolution digital elevation model was used to model the impact of local topography and shading by surrounding terrain on solar radiation. A sunshine‐based model was adopted to simulate radiation under the influence of clouds. A GIS‐based solar radiation model that incorporates albedo, shading by surrounding terrain, and variations in cloudiness was used to address the spatial variability of these factors in mountainous terrain. Compared with other independent solar radiation products, our model generated a more reliable solar radiation product over rugged terrain, with an R 2 of 0.88 and an RMSE of 2.55 MJ m −2 day −1 . The improved solar radiation products and open source app can be used further in practice or scientific research.